The distribution and abundance of baboons (Papio Anubis) in Sambisa game reserve (2015)
Base line information on animal population distribution and abundance is crucial to planning and implementation of effective management strategies for the conservation of species. There is paucity of information on the distribution and abundance of papio anubis in Sambisa game reserve. Therefore, this study was carried out to obtain information on estimate, population structure and abundance of the species, as well as habitat disturbances. The line transect sampling method was used for the enumeration. The data obtained was analyzed using the software package DISTANCE 6.0 to determine population density estimate. The result indicated that Baboon population was concentrated in three ranges of the Reserve a Range has suffered habitat disturbances resulting into insignificant number of primates. The mean encounter rates (MERs) for the species was 1.85km-1. Baboon had the estimated density of about 12km-2. There was a significant difference in the pattern of the species densities for morning and evening counts. The mean encounter rate for Baboon were 1.15 km-1 (n=110) and 0.71 km-1 (n= 68) individual animals for morning and evening sightings respectively. The relative density for the primate species across the four ranges in the reserve revealed that Baboon was not recorded in Balda range and only 2 individuals sighted in Jeltere. Kwada and yuwe range have the highest abundance of 119 and 57 individuals sighted respectively. The population structure shows declining trend as number of juveniles was relatively lower than adult population. However, the relatively higher percentage of female adults may result in population growth, if majority of them are within the breeding age. The highest numbers of primate species were found in the centre of the reserve (Kwada and Yuwe) where habitat disturbances were controlled.